Integrating Literary Works as the Local Content of ELT Materials for Undergraduate Students - Pratiwi Amelia; Agci Hikmawati (English Language Teaching Educational Journal, 2019)
The objective of this study is to design English materials for undergraduate students. In designing the materials, the writers focused on the general English materials integrated with Bangkanese’ Folks as one of the literary works existing in Bangka Belitung Province, Indonesia. This idea was based on the writers’ awareness to introduce local values to the students. Thus, the existing literary works were taken and modified by the writers to meet the purpose of the research.  The writers used the theory of Hutchinson and Waters (1987) and Borg & Gall (1989). The theory offered six steps, namely need analysis, writing syllabus, developing materials, trying-out materials, evaluating materials, revision, and writing the final draft. The participants of the research were 37 students studying in one of the private colleges in Bangka Belitung Province. These participants were chosen randomly. The designed ELT materials integrated the English lessons and the local folktales and culture. The integration was intended to improve the students’ communicative competence of both productive and receptive skills. Furthermore, it was expected that the designed materials were able to encourage the students to communicate more communicatively and appropriately in their social context.